Research Program, Paradigm or Problematic? Three Ways of Reading Max Weber - Jóhann Páll Árnason (Historicka Sociologie, 2025)
This paper discusses ways of understanding the unity of Max Weber’s work and argues that the concept of problematic is more suitable than those commonly used in contemporary philosophy of science, such as paradigm or research program. The concept of problematic implies a less closed and integrated framework than the other two; it also places more emphasis on the problems of conceptualization. All these features make it a more adequate key to Max Weber’s eminently multi-disciplinary and multi-perspectivistic but very unfinished project. The reference to a problematic connotes both strengths and weaknesses; the strengths have to do with Weber’s exceptional ability to tackle diverse domains of research and theorizing in an original and productive way, the weaknesses with unclear connections between them and with insufficient grounding in basic concepts. These claims are backed up by closer examination of Weber’s sociology of rule, especially his analysis of changing historical relations between political and religious power. Insights gained through this approach to the political sphere can then serve to conceptualize the cultural and economic ones in a way that builds on Weber’s work but goes beyond its historically conditioned horizons.